2004
DOI: 10.1128/aem.70.6.3305-3312.2004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Chemical, and Genetic Diversity of Tropical Marine Cyanobacteria Lyngbya spp. and Symploca spp. ( Oscillatoriales )

Abstract: Although diverse natural products have been isolated from the benthic, filamentous cyanobacterium Lyngbya majuscula, it is unclear whether this chemical variation can be used to establish taxonomic relationships among disparate collections. We compared morphological characteristics, secondary-metabolite compositions, and partial 16S ribosomal DNA (rDNA) sequences among several collections of L. majuscula Gomont, Lyngbya spp., and Symploca spp. from Guam and the Republic of Palau. The morphological characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 62 publications
(71 reference statements)
1
48
0
1
Order By: Relevance
“…Taxonomic studies of the Oscillatoriales, which includes many chemically rich species in genera such as Lyngbya, Oscillatoria, and Phormidium, have conventionally been based on morphological characteristics, including cell length and width, colony formation, extracellular sheath width, and pigmentation. Unfortunately, these diagnostic features exhibit plasticity in response to environmental parameters such as salinity, turbidity, and nutrient content (44,54,59). Molecular approaches to taxonomy, based on nitrogenase (nifH) and 16S rRNA gene sequences (18,24,25,59,63,64) and random amplified polymorphic DNA analysis (6,40), have revealed enormous phylogenetic diversity among environmental cyanobacteria not indicated by morphological classifications, suggesting that cyanobacterial taxonomy remains widely unresolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomic studies of the Oscillatoriales, which includes many chemically rich species in genera such as Lyngbya, Oscillatoria, and Phormidium, have conventionally been based on morphological characteristics, including cell length and width, colony formation, extracellular sheath width, and pigmentation. Unfortunately, these diagnostic features exhibit plasticity in response to environmental parameters such as salinity, turbidity, and nutrient content (44,54,59). Molecular approaches to taxonomy, based on nitrogenase (nifH) and 16S rRNA gene sequences (18,24,25,59,63,64) and random amplified polymorphic DNA analysis (6,40), have revealed enormous phylogenetic diversity among environmental cyanobacteria not indicated by morphological classifications, suggesting that cyanobacterial taxonomy remains widely unresolved.…”
mentioning
confidence: 99%
“…Unfortunately, these diagnostic features exhibit plasticity in response to environmental parameters such as salinity, turbidity, and nutrient content (44,54,59). Molecular approaches to taxonomy, based on nitrogenase (nifH) and 16S rRNA gene sequences (18,24,25,59,63,64) and random amplified polymorphic DNA analysis (6,40), have revealed enormous phylogenetic diversity among environmental cyanobacteria not indicated by morphological classifications, suggesting that cyanobacterial taxonomy remains widely unresolved. As a result, it has been a challenge to identify species-specific patterns of bioactive compound production in the Oscillatoriales.…”
mentioning
confidence: 99%
“…Although well over 100 compounds have been isolated from L. majuscula and other marine species of Lyngbya (Thacker and Paul, 2004), very few have been reported from freshwater species, and, to the authors' knowledge, this is the first such compound to be purified and characterized from an Everglades isolate. That said, a survey of microalgae (Lewis et al, 2004) in the Everglades-Florida Bay transition zone identified Lyngbya as one of the dominant members of the benthic and periphyton communities in this area.…”
Section: Discussionmentioning
confidence: 86%
“…A number of compounds from Lyngbya are currently being investigated with respect to potential pharmaceutical development, as well as to human and environmental health implications of these compounds as naturally occurring toxins (Moore, 1996;Gerwick et al, 2001;Mayer and Gustafson, 2003;Shimizu, 2003;Thacker and Paul, 2004). Pharmacological activity of such Lyngbya-derived compounds ranges from microtubule inhibitors, such as curacin A (Gerwick et al, 1994), to potent sodium channel blockers and activators, such as kalkitoxin (Wu et al, 2000) and antillatoxin (Li et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation